Characteristics and proteomic analysis of pyrene degradation by Brevibacillus brevis in liquid medium. (July 2017) - Wei, Kun; Yin, Hua; Peng, Hui; Liu, Zehua; Lu, Guining; Dang, Zhi
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are widely spread in various ecosystems and are of great concern due to their potential toxicity, mutagenicity and carcinogenicity. Bioremediation has been proposed as an effective approach to remove PAHs. In this study, the physiological responses and proteome of Brevibacillus brevis under exposure to pyrene, a four-ring compound from PAHs family, were investigated. The changes of cell viability of B. brevis were observed during the degradation of pyrene by means of flow cytometry. The results indicated that pyrene stimulated superoxide dismutase (SOD) activity from 93.9 to 100.6 U mg −1 prot, whereas inhibited catalase (CAT) activity from 29.1 to 20.3 U mg −1 prot. The main compositions of B. brevis changed during pyrene degradation, with the proportion of unsaturated fatty acids increased by 13.4%. In addition, we performed a proteomic approach (two-dimensional gel electrophoresis and MALDI-TOF/TOF-MS) in order to explore how B. brevis survived upon treatment with pyrene. It was showed that the expression of 13 proteins increased whereas 10 other decreased after pyrene-treatment. The differentially expressed proteins were identified and the results indicated that they were involved in multiple biological processes including energy metabolism, biosynthesis, transmembrane transport and oxidative stress. Overall, these findings offered a new insights into the cellular response strategy developed by B. brevis to overcome the pyrene stress. Highlights: The total cell count significantly increased during pyrene degradation. Pyrene stimulated SOD activity but inhibited CAT activity. Pyrene promoted the proportion of unsaturated fatty acids. ATP synthase and ATP-dependent RNA helicase were up-regulated under pyrene stress.